2011
DOI: 10.1016/j.bpj.2011.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell Imaging at Nanometer Resolutions Using Fast and Slow Focused Helium Ions

Abstract: Observations of the interior structure of cells and subcellular organelles are important steps in unraveling organelle functions. Microscopy using helium ions can play a major role in both surface and subcellular imaging because it can provide subnanometer resolutions at the cell surface for slow helium ions, and fast helium ions can penetrate cells without a significant loss of resolution. Slow (e.g., 10-50 keV) helium ion beams can now be focused to subnanometer dimensions (∼0.25 nm), and keV helium ion micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…an electron column is added to image the FIB fabrication region using the standard SEM technique. High-resolution imaging is also possible using a focused He-ion beam [79,80].…”
Section: Focused Ion Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…an electron column is added to image the FIB fabrication region using the standard SEM technique. High-resolution imaging is also possible using a focused He-ion beam [79,80].…”
Section: Focused Ion Beamsmentioning
confidence: 99%
“…Given that the scattering of helium ions is very sensitive to the mass of the target atoms (particularly for high-atomicnumber (ions), incubating heavy ion nanoparticles (NPs) inside the sample is needed. Chen et al reported on the 3D whole-cell imaging of gold nanoparticle in cell biological system through the combination of STIM for imaging the cell structure [79], forward STIM for lateral image of gold NPs, and Rutherford backscattering spectrometry (RBS) for depth profiles of gold NPs. The spatial resolutions of STIM and RBS are ~25−30 nm and 200−300 nm, respectively.…”
Section: Focused Helium Ion Beams For 3d Nano Imagingmentioning
confidence: 99%
“…Nor can they distinguish endogenous metal from metal ions in, or sourced from, the metal oxide particles. However, the best resolutions achieved with nuclear microscopy are below 50 nm (Chen et al 2011). Such level of resolution would possibly enable individual particle detection and visualization on the basis of density contrast, which is equivalent to TEM.…”
Section: Methods For Analysing Samplesmentioning
confidence: 97%
“…The gas field ionization source has ultra-high brightness, and a very small beam defining aperture may be used, minimizing spherical and chromatic aberrations and resulting in higher depth of field and a estimated resolution of 0.35 nm (Joy, 2013;Hlawacek et al, 2014;Joens et al, 2013). Besides that, when the surface of the sample is bombarded by He + , the penetration of the beam is smaller, when compared to an electron beam accelerated to 30 kV, improving the resolution (Chen et al, 2011). The secondary electron yield is much higher than in SEM, giving to the images a better signal-to-noise ratio (Inai et al, 2007;Joens et al, 2013).…”
Section: Introductionmentioning
confidence: 98%